Inter-relationsmp between Geology, Soil and Vegetation in Raipur Range of Mussoorie Forest Division, Uttaranchal - Raina, A. K.; Jha, M. N. (Indian Forester, 2005)
The relationship between geology, soil and vegetation have been evaluated in Raipur range of Mussoorie Forest Division (Uttaranchal). The findings of the study show that floristic composition and soils have some relationship with parent material. It has been observed that Mollisols occur on dolomitic limestones (Dwara) or on limestones interbedded with shales (Ladpur, Raipur, Rajpur and parts of Ringalgarh) whereas Inceptisols occur on quartzites (Mahipur and parts of Sripur) and on phyllite, slate and limestone (Ringalgarh). The study further indicated on the basis of soil and mineralogical data that Quercus leucotrichophora and Pinus roxburghii forests thrive well on Inceptisols whereas Shorea robusta, Dalbergia sissoo and scrub forests grow well on Mollisols. Relief and age acting on geology of Raipur range of Mussoorie forest division govern the existing soil formation whereas altitude and climate besides other soil forming factors impact geology and give rise to natural vegetation. Climate and aspect of a particular site have given rise to the various pedogenic processes and floristic composition. It was, however, inferred on the basis of soil as weB as mineralogical data that geology, vegetation and soil are in stable relationship with each other and such studies should also be carried out in different ranges for a comprehensive knowledge of these inter-relationships.